Risk assessment framework for exposure of cargo and ports to natural hazards and climate extremes. Issue 1 (2nd January 2017) - Lam, Jasmine Siu Lee; Lassa, Jonatan A.
ABSTRACT: There is an increase in risks and catastrophic losses in maritime transport including ports and cargo. Significant losses have been associated with large scale natural hazards, such as earthquakes, tsunami, cyclones, and other extreme weather events. This paper identifies the main gaps in understanding maritime risks in transportation research. The gaps are attributed to insufficient empirical work available from the maritime transport and logistics research community to guide multi-risk and natural hazards impact assessment on seaport and cargo. In addition, disaster studies communities have barely made adequate efforts to understand and assess port and cargo risks arising from multi-hazards and disaster events. This paper examines existing conceptual frameworks concerning exposure and risk assessments of natural catastrophe's impacts. Furthermore, the paper identifies trends and gaps in risk assessment frameworks in the field of disaster studies that can be beneficial for maritime risk research. The authors propose a new risk assessment framework that can guide future research and multi-hazard risk assessment processes at different scales of maritime risks.